2017
DOI: 10.1177/0954405417738283
|View full text |Cite
|
Sign up to set email alerts
|

The influence of oil source pressure fluctuation on the waviness error of potassium dihydrogen phosphate in ultra-precision machining

Abstract: The performance of potassium dihydrogen phosphate optical components is very sensitive to the waviness error. The time-varying oil source pressure leads to dynamic change in the eccentricity of hydrostatic slide; waviness errors can be induced on the finished surface of potassium dihydrogen phosphate consequently. The relationship between unsteady oil source pressure and the waviness errors of potassium dihydrogen phosphate is studied in this article. A mathematical model is built to calculate the displacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…It was further validated with mathematical solutions by Zhang et al 11 Moreover, Deng et al 12 found a kind of low-frequency waviness, who is generated by the deformation of spindle system because of air pressure fluctuations. Similarly, waviness also steams from oil pressure fluctuations stated by Gao et al 13 In particular, the dynamic performance of the flycutting machine tool contributes significantly to medium-frequency errors. In the study by Chen et al, 14 wavelet method was adopted for surface analysis.…”
Section: Introductionmentioning
confidence: 89%
“…It was further validated with mathematical solutions by Zhang et al 11 Moreover, Deng et al 12 found a kind of low-frequency waviness, who is generated by the deformation of spindle system because of air pressure fluctuations. Similarly, waviness also steams from oil pressure fluctuations stated by Gao et al 13 In particular, the dynamic performance of the flycutting machine tool contributes significantly to medium-frequency errors. In the study by Chen et al, 14 wavelet method was adopted for surface analysis.…”
Section: Introductionmentioning
confidence: 89%
“…They reported that the low-frequency vibration influences the surface roughness error, while the high-frequency vibration affects the figure error in fly-cutting process. Furthermore, Gao et al pointed out that the fluctuation of the oil source pressure and the flow status of the film of the aerostatic spindle will also affect the figure error in fly-cutting process [91,92].…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…He and Zong 16 described the mechanism of multi-frequency vibration on the optical performance of diamond-turned workpieces, and he used well-established two-step process technology to reduce the effect of vibration, which was experimentally proved to be highly effective. 17,18 Gao et al 19 investigated the relationship between the ripple errors of machined surfaces and oil source pressure fluctuations and demonstrated that an unsteady oil source pressure had a remarkable effect on the topography of a workpiece. Wei et al 20 theoretically and experimentally investigated the dynamic characteristics of air spindles and their effect on medium-frequency ripples in machined surface shapes.…”
Section: Introductionmentioning
confidence: 99%